2013
DOI: 10.7705/biomedica.v34i1.1442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la relación de actividad física autorreportada con el síndrome metabólico y sus componentes en mujeres aparentemente sanas

Abstract: Introduction:The metabolic syndrome, a set of metabolic anomalies that include insulin resistance, central obesity, dyslipidemia, hypertension and inflammation, is an important tool to explore factors associated to cardiometabolic disease. Objective: The aim of this study was to evaluate the relationship of the levels of self-reported physical activity and the International Physical Activity Questionnaire items and the metabolic syndrome and the variables related to cardiovascular risk in 89 women. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…According to the definition of the National Cholesterol Education Program–Adult Treatment Panel III of the United States, the prevalence of MetS in adults was: 32% in Hispanic Americans; 22% in African Americans; and 24% in European Americans [3]. In Colombia, Martínez-Torres et al [32] reported the predisposing factors for having a MetS included: being male, over 25 years old and overweight or obese, all of them related to metabolic disorders as previously described in apparently healthy women [31]. In addition, the public policy recommendations also highlight the need for healthy adults to have an activity plan that integrates preventative and therapy recommendations [4042].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the definition of the National Cholesterol Education Program–Adult Treatment Panel III of the United States, the prevalence of MetS in adults was: 32% in Hispanic Americans; 22% in African Americans; and 24% in European Americans [3]. In Colombia, Martínez-Torres et al [32] reported the predisposing factors for having a MetS included: being male, over 25 years old and overweight or obese, all of them related to metabolic disorders as previously described in apparently healthy women [31]. In addition, the public policy recommendations also highlight the need for healthy adults to have an activity plan that integrates preventative and therapy recommendations [4042].…”
Section: Introductionmentioning
confidence: 97%
“…Although the epidemiologic transition and epidemic of CVD have been well documented in Latin Americans [2931], relatively little research on their PA [3234] and physical fitness exists. Moreover, Latin American countries [6, 7] have a similar or even greater prevalence of MetS among adults than developed countries [8].…”
Section: Introductionmentioning
confidence: 99%